Life as Robinsonade: Reflections on the Chronopoetics of Lutz Seiler's Kruso. (2nd October 2017) - Fuchs, Anne
Abstract : This article analyzes the representation of poetic time in Lutz Seiler's acclaimed novel Kruso . It shows how Seiler's novel adopts the narrative structure of the robinsonade to test the small utopia of an alternative existence within the borders of the GDR shortly before the fall of the Berlin wall. The island of Hiddensee is depicted in the novel as a sort of GDR-Tahiti for GDR social drop-outs who are engaging in a 'Zeitspiel' in opposition to the mainland at the very moment when the events of 1989 produced massive geo-political upheavals. The continual use of literary citation underpins the chronopoetic game of Seiler's protagonists who, by fictionalising their world, attempt, at least temporarily, to flee the bleakness of their lived socialist realities. Enacting Eigenzeit through the mode of fiction, the novel replaces the big political utopia with the small utopia. For the protagonists of this novel, the future is no longer their horizon of orientation.